Targeting Akt/CREB/BDNF signaling pathway by ginsenosides in neurodegenerative diseases: A mechanistic approach - Seyede Nazanin Zarneshan; Sajad Fakhri; Haroon Khan (Elsevier, 2022)
Neurodegenerative diseases (NDDs) are leading causes of death and morbidity in the elderly worldwide. From the mechanistic/pathological view, oxidative stress, inflammation, and apoptosis are responsible for the etiology of neuronal diseases, and play detrimental roles in neuronal cell death and neurodegenerative processes. The diverse pathophysiological pathways influencing NDDs necessitate the discovery of pivotal dysregulated signaling mediators. The current review describes essential functions of protein kinase B (Akt)/cyclic adenosine monophosphate (cAMP) response element-binding protein (CREB)/brain-derived neurotrophic factor (BDNF) pathway as possible therapeutic targets in the pathogenesis of NDDs. Consequently, finding new multi-target agents in regulating Akt/CREB/BDNF and thus associated downstream pathways is a critical factor in combating NDDs. Because of their neuroprotective properties, dietary phytochemicals have shown to be popular nutritional therapy methods. Ginsenosides, the most active ingredient of ginseng, and a secondary metabolite of steroid glycosides and triterpene saponins have been found to have a number of protective effects on the central nervous system (CNS). The protective roles of ginsenosides in CNS are potentially passing through Akt/CREB/BDNF pathway towards neuroprotective responses. In the present study, Akt/CREB/BDNF pathway is targeted by ginsenosides and associated nanoformulations towards potential neuroprotective effects.